PENGGUBALAN KURIKULUM BERSEPADU SEKOLAH MENENGAH (KBSM) DI MALAYSIA: MASLAHAH DALAM RUJUKAN MAZHAB - Jasni Sulong (Universitas Islam Negeri Sumatera Utara Medan, 2020)
The drafting on the New Curriculum of Secondary School (KBSM) for the Islamic studies as a core and elective subject was based on the Shafi'i Mazhab. This is because Malaysia prefers the teaching of Shafi‟ite school. Many of the school‟s writings were served as the main reference in promulgating laws. This has led to inflexibility as well as difficulty in practicing some cases that do not fit to the viewpoint of the Shafi'ite. Times have changed as well as local practices, thus it would troublesome to confine on only particular sect of teaching. As such, the study was aimed at identifying the influence of the Shafi‟ite teaching in the school curriculum in Malaysia and to what extent other than the school‟s teaching will revealed to students. The scope of study is the course of Islamic studies under the New Curriculum of Secondary School (KBSM). This study is qualitative way as the data will be collected through library and interview research. By analyzing the curriculum using inductive and deductive methods, it was found that the curriculum has given inclination to the Shafi‟te teaching for the benefit as well as consistency in the practice of Islamic religion in Malaysia. However, there are certain topics that also choose the view of non Shafi‟ite for the reason of suitability and appropriateness. This approach is consistent with states fatwa in Malaysia. The results show that the KBSM curriculum is not confined to the Shafi‟ite teaching per se, and its application benefited the community.